Double-layer double-high type electrode, reserve lithium battery and preparation method of reserve lithium battery
By using double-layer double-height electrodes, combining energy-type and power-type active materials, and controlling the conductive network, the existing lithium storage batteries are solved, and the problem of difficult to meet high energy density, high magnification and fast activation at the same time, achieving efficient battery performance.
Patent Information
- Application Number
- CN202411615607.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Existing lithium storage batteries are difficult to meet the requirements of high energy density, high magnification and fast activation at the same time.
A double-layer double-height type electrode is adopted, including a current collector, a first active layer and a second active layer. The first active layer contains an energy-type active material, and the second active layer contains a pre-charged power-type active material. By regulating the content and porosity of the conductive agent and the binder, an efficient conductive network is constructed.
It has achieved fast activation, high energy density and good rate performance, and comprehensively utilizes energy-type active materials with high energy density and power-type active materials with good rate performance, which has improved the energy density and rate performance of the electrode.
Smart Images

Figure CN119542341A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reserve lithium batteries, and in particular to a double-layer double-high type electrode, a reserve lithium battery and a preparation method thereof. Background Art
[0002] Reserve lithium batteries are batteries in which the dry cells and electrolyte are stored separately before discharge. When discharged, the dry cells are brought into contact with the electrolyte by an activation mechanism or external mechanical impact, thereby generating an electrochemical reaction to provide external power. The dry cells are kept in an inert environment during long-term storage, so they have relatively better safety and storage life. Among reserve batteries, reserve lithium batteries have a higher energy density than water-activated batteries and thermal batteries, and are expected to be used as high-performance alternatives in special fields such as underwater equipment and fuses.
[0003] In addition to energy density, activation time and rate performance are also key performance indicators of reserve batteries. Activation time refers to the time interval from the injection of electrolyte into the battery to the time when the battery can begin to discharge under load. The shorter the activation time and the greater the discharge rate, the better the rapid response capability of the reserve battery, and the better it can meet the requirements of future new equipment.
[0004] Reserve lithium batteries mainly include lithium thionyl chloride batteries, lithium vanadium pentoxide batteries and lithium sulfur dioxide batteries, but it is difficult for the above batteries to simultaneously meet the requirements of high energy density (≥200Wh / kg), high rate (≥5C) and fast activation (≤10s). Summary of the invention
[0005] The object of the present invention is to provide a double-layer double-high type electrode, a reserve lithium battery and a preparation method thereof to solve the problems in the background technology.
[0006] The technical solution of the present invention includes: a double-layer double-high type electrode, which includes: a current collector, a first active layer and a second active layer, the first active layer is located between the current collector and the second active layer, the first active layer contains energy-type active materials, and the second active layer contains pre-charged power-type active materials, and the open circuit voltage difference between the energy-type active materials and the pre-charged power-type active materials is ≤0.5V.
[0007] Specifically, the energy-type active material includes Cr2O5, Cr3O8 and Cr8O 21 At least one of .
[0008] Specifically, the pre-charged power type active material is obtained by pre-charging the power type active material with an initial state of charge = 0; the power type active material with an initial state of charge = 0 includes LiCrO2, LiCoO2, LiNiO2, LiNi a Cob Mn (1-a-b) O2 and LiNi a Co b Al (1-a-b) At least one of O2.
[0009] Specifically, the first material layer contains a first conductive agent, the second material layer contains a second conductive agent, and the proportion of the first conductive agent in the first material layer is higher than the proportion of the second conductive agent in the second material layer.
[0010] Specifically, the porosity of the first material layer is less than that of the second material layer; the porosity of the first material layer is 25% to 40%, and the porosity of the second material layer is 35% to 45%.
[0011] Specifically, the first material layer contains a first binder, and the mass ratio of the energy-type active material, the first conductive agent and the first binder is (87-96): (2-6): (2-7).
[0012] Specifically, the second material layer contains a second binder, and the mass ratio of the pre-charged power-type active material, the second conductive agent and the second binder is (92-98): (1-4): (1-4).
[0013] Specifically, a plurality of seepage diversion grooves are provided on the surface of the second material layer facing away from the first material layer, and both ends of the seepage diversion grooves extend to the side edges of the second material layer respectively. The total area of the plurality of seepage diversion grooves accounts for 1% to 20% of the total area of the second material layer.
[0014] The technical solution of the present invention also includes: a method for preparing a double-layer double-height electrode, which includes the steps of:
[0015] The power type active material with an initial state of charge = 0 is mixed with a second conductive agent and then pre-charged to obtain a pre-charged power type active material;
[0016] Using an energy-type active material, a first conductive agent and a first binder to prepare a first material layer slurry with a solid content of 40 wt% to 60 wt%, coating the first material layer slurry on the surface of a current collector, and drying to obtain a first material layer;
[0017] Using the pre-charged power-type active material, the second conductive agent and the second binder to prepare a second material layer slurry with a solid content of 50wt% to 70wt%, coating the second material layer slurry on the surface of the first material layer, drying and compacting to obtain the second material layer;
[0018] On the surface of the second material layer, a plurality of liquid seepage guide grooves are constructed by laser etching to obtain a double-layer double-height electrode.
[0019] The technical solution of the present invention also includes: a reserve lithium battery, the positive electrode of which adopts the double-layer double-high type electrode as described above.
[0020] The invention has the beneficial effects of providing a double-layer double-high type electrode for a reserve lithium battery with fast activation, high energy density and good rate performance, comprehensively utilizing energy-type active materials with high energy density and power-type active materials with good rate performance, and improving the energy density and rate performance of the electrode; in order to prevent side reactions from occurring inside the electrode, the open circuit voltage difference between the energy-type active material and the pre-charged power-type active material is controlled within 0.5V. By arranging the first material layer close to the current collector and regulating the content of the first conductive agent in the first material layer, the electron transmission efficiency of the first material layer is improved, and by regulating the proportion of the first conductive agent in the first material layer and the proportion of the second conductive agent in the second material layer, the differentiated requirements of different positive electrode materials for the conductive network are met, an efficient conductive network is constructed, and the discharge performance of the battery is improved; comprehensively considering the particle size difference of the active material itself, and regulating the content of the first conductive agent and the second conductive agent, the porosity of the first material layer is less than the porosity of the second material layer after the pole piece is compacted, and a seepage diversion groove is dug on the surface of the second material layer, and the electrolyte infiltration rate of the electrode is improved under the premise of ensuring the energy density and rate performance of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a longitudinal sectional view of an embodiment of the present invention;
[0022] Figure 2 is a top view of embodiment 1 of the present invention;
[0023] Figure 3 It is a top view of embodiment 2 of the present invention.
[0024] In the figure:
[0025] 1. Current collector; 2. First material layer; 3. Second material layer; 4. Liquid seepage guide groove. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with embodiments and drawings:
[0027] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and comparative examples, and are not intended to limit the scope of protection of the present invention. It should be particularly noted that there may be multiple names for the same organic structure, as long as the structure is within the scope of this patent, it belongs to the protection object of this patent.
[0028] Unless otherwise defined, the raw materials, reagents, etc. in the following examples can be purchased from the market or prepared according to reported methods.
[0029] The double-layer double-high type electrode provided in the embodiment of the present invention is mainly used in the field of lithium storage batteries, which contains two positive electrode material layers. Referring to the accompanying drawings, its structure includes a current collector 1, a first material layer 2 and a second material layer 3. The current collector is a sheet, and the first material layer 2 is respectively constructed on both sides, and the separated sides of the two first material layers 2 are respectively constructed with the second material layer 3. The first material layer 2 contains energy-type active materials, a first conductive agent and a first binder, and the second material layer 3 contains pre-charged power-type active materials, a second conductive agent and a second binder. The energy-type active materials with high energy density and the power-type active materials with good rate performance are comprehensively utilized to improve the energy density and rate performance of the electrode. Since the energy-type active materials with high energy density have poor electronic conductivity, placing them in the first material layer 2 close to the current collector 1 can shorten the electronic conduction distance and improve the electronic transmission efficiency of the electrode. However, since different types of active materials are selected in the first material layer 2 and the second material layer 3, in order to prevent side reactions from occurring inside the electrode, it should be ensured that different active materials have similar electrode potentials or similar discharge voltage ranges. Therefore, when constructing a double-layer double-high electrode, it should be ensured that the open circuit voltage between the energy-type active material and the pre-charged power-type active material is ≤0.5V.
[0030] During implementation, the energy-type active materials can be selected from Cr2O5, Cr3O8 and Cr8O with high energy density. 21 One or more of the above, the power type active material can be selected from LiCrO2, LiCoO2, LiNiO2, LiNi with high rate performance a Co b Mn (1-a-b) O2 and LiNi a Co b Al (1-a-b) One or more of O2, among which the initial charge state of the chromium-based oxide is greater than 0 and can be discharged directly, and the initial charge state of the power-type active material is equal to 0 and cannot be discharged directly. Therefore, the power-type active material needs to be pre-charged to delithiate it to a charge state greater than 0.
[0031] When precharging the power type active material, the precharge cut-off voltage of the power type active material is controlled according to the open circuit voltage difference between the energy type active material and the precharged power type active material ≤ 0.5V and the properties of the power type active material itself. The energy type active material selected in this embodiment is chromium-based oxide, and the open circuit voltage of chromium-based oxide is generally 3.3-4.0V (relative to Li / Li +), and the power type active material will have a small loss after pre-charging, so the specific material selection can be comprehensively compared to control the pre-charge cut-off voltage of the power type active material to 3.8 ~ 4.4V (relative to Li / Li + ), the charging current is controlled at 0.01~0.2C.
[0032] Since energy-type active materials have high energy density and poor rate performance, while power-type active materials have low energy density and good rate performance, in order to improve the electron transmission efficiency of the first material layer 2, build an efficient conductive network, and improve the discharge performance of the battery, in this embodiment, the proportion of the first conductive agent in the first material layer 2 is higher than the proportion of the second conductive agent in the second material layer 3.
[0033] The first conductive agent and the second conductive agent are respectively selected from at least one of conductive carbon black, porous carbon and carbon nanotubes. The proportion of the first conductive agent in the first material layer 2 and the proportion of the second conductive agent in the second material layer 3 can be determined according to the specific materials of the first conductive agent and the second conductive agent.
[0034] In addition to energy density and rate performance, activation time is also an important performance indicator of storage lithium batteries. In the electrodes of storage lithium batteries, the porosity of each material layer will affect the infiltration rate of the electrolyte, and then affect the activation time of the battery. The larger the porosity, the faster the electrolyte infiltrates, and the shorter the activation time of the battery. However, the increase in porosity is often accompanied by a decrease in the content of components in the material layer. The second material layer 3 is located in the outermost layer of the electrode and is the first part to contact the electrolyte when the battery is activated, while the first material layer 2 is the main contributor to the energy density of the electrode. Taking the above factors into consideration, the porosity of each material layer in this embodiment is regulated as follows: the porosity of the first material layer 2 is less than the porosity of the second material layer 3. By designing the gradient of the porosity in the thickness direction of the electrode, the infiltration rate of the electrolyte is increased, the activation time of the battery is shortened, and the content of the components in each material layer, especially the content of the energy-type active material and the first conductive agent in the first material layer 2, is not excessively sacrificed.
[0035] In this embodiment, the particle size of the energy-type active material is smaller than that of the power-type active material. By adjusting the content of the first conductive agent and the second conductive agent in each material layer and combining the influence of the particle size of the energy-type active material and the power-type active material themselves, the first material layer 2 and the second material layer 3 have different porosities under the same rolling pressure. Preferably, the mass ratio of the energy-type active material, the first conductive agent and the first binder in the first material layer 2 is (87-96): (2-6): (2-7), and the mass ratio of the pre-charged power-type active material, the second conductive agent and the second binder in the second material layer 3 is (92-98): (1-4): (1-4). The first material layer 2 and the second material layer 3 are placed on the current collector 1 by a slurry coating method, and the electrode is rolled after drying, and the compaction density is controlled at 2.0-3.3 g / cm 3 The porosity of the first material layer 2 is 25% to 40%, and the porosity of the second material layer 3 is 35% to 45%.
[0036] The first binder, the second binder, and the solvent used in slurrying in this embodiment are all commonly used materials in the art and can be selected according to specific needs. For example, the first binder and the second binder can be polyvinylidene fluoride, and the solvent can be N-methylpyrrolidone. During implementation, adjustments can be made according to specific needs. In order to improve the bonding strength between the material layer and the current collector 1, the proportion of the first binder in the first material layer 2 can be appropriately increased.
[0037] In order to further improve the electrolyte infiltration rate of the electrode and shorten the activation time of the battery, in this embodiment, a plurality of seepage guide grooves 4 are provided on the outer surface of the second material layer 3, that is, the surface away from the first material layer 2. The seepage guide grooves 4 extend in the horizontal, vertical or oblique direction, and both ends thereof extend to the side edges of the second material layer 3, respectively. Through the seepage guide grooves 4, the rapid liquid absorption capacity of the electrode is improved. Taking into account the activation time and structural strength of the electrode, in this embodiment, the width of the seepage guide grooves 4 is controlled to be 0.1-2 mm, and the depth is controlled to be 5-40 μm. The distribution density of the seepage guide grooves 4 can be configured according to actual needs, but the total area of the plurality of seepage guide grooves 4 should be controlled to account for 1%-20% of the total area of the second material layer 3.
[0038] This embodiment also provides a method for preparing the above-mentioned double-layer double-height electrode, comprising the following steps:
[0039] (1) A power type active material having an initial state of charge = 0 is mixed with a second conductive agent and then pre-charged to obtain a pre-charged power type active material.
[0040] In this step, the specific pre-charging method is: mixing the power-type active material with an initial charge state = 0 with the second conductive agent, adding an appropriate amount of electrolyte, and stirring the above substances at a high speed of 3000 rpm to obtain a paste positive electrode slurry; pouring the paste positive electrode slurry into a charging device made of insulating material, inserting a current collector made of aluminum metal, and covering the surface of the paste positive electrode slurry with a polyolefin material diaphragm, the diaphragm thickness is 24μm, and the diaphragm size should be larger than the inner cavity of the charging device so that the paste positive electrode slurry will not overflow from under the diaphragm; after adding an appropriate amount of electrolyte on the upper part of the diaphragm, a metal lithium sheet containing a current collector is placed as the negative electrode, and the cover of the charging device is covered to ensure internal sealing; using a charging and discharging device for pre-charging, the pre-charging current and the charging cut-off voltage are determined according to the specific selection of the power-type active material and the energy-type active material; after charging is completed, the device is disassembled to take out the positive electrode material paste, and after cleaning with DMC, it is dried in an oven at 40°C for 5h.
[0041] (2) A first material layer slurry with a solid content of 40 wt% to 60 wt% is prepared by using an energy-type active material, a first conductive agent and a first binder, and the first material layer slurry is coated on the surface of a current collector and dried to obtain a first material layer.
[0042] In this step, the coating amount of the first material layer slurry is controlled at 5-30 mg / cm 2 .
[0043] (3) Using the pre-charged power-type active material, the second conductive agent and the second binder to prepare a second material layer slurry with a solid content of 50wt% to 70wt%, the second material layer slurry is coated on the surface of the first material layer, and the second material layer is compacted after drying to obtain the second material layer.
[0044] In this step, the coating amount of the second material layer slurry is controlled at 5-30 mg / cm 2 , compacted density is 2.0~3.3g / cm 3 .
[0045] (4) On the surface of the second material layer, a plurality of liquid seepage guide grooves are constructed by laser etching to obtain a double-layer double-height electrode.
[0046] In this step, during laser etching, the laser power is 2W to 30W, the wavelength is 200nm to 1um, the frequency is 10 to 50kHz, and the etching speed is 200 to 5000mm / s.
[0047] This embodiment also provides a reserve lithium battery. The positive electrode of the reserve lithium battery adopts the above-mentioned double-layer double-high type electrode, and the negative electrode, electrolyte and assembly method are the same as those of a conventional reserve lithium battery.
[0048] The following are specific embodiments of the present invention.
[0049] Example 1
[0050] Preparation of double-layer double-height electrode
[0051] (1) LiCoO2, conductive carbon black and carbon nanotubes were weighed in a mass ratio of 96:1.5:0.5, and after adding an appropriate amount of electrolyte, the above substances were stirred at a high speed of 3000 rpm to obtain a paste positive electrode slurry; the paste positive electrode slurry was poured into a charging device made of insulating material, and a current collector made of aluminum metal was inserted. A polyolefin diaphragm was covered on the surface of the paste positive electrode slurry, and the thickness of the diaphragm was 24 μm. The size of the diaphragm should be larger than the inner cavity of the charging device so that the paste positive electrode slurry would not overflow from under the diaphragm; after adding an appropriate amount of electrolyte on the upper part of the diaphragm, a metal lithium sheet containing a current collector was placed as the negative electrode, and the cover of the charging device was covered to ensure internal sealing; a charging and discharging device was used for pre-charging, and the pre-charging current was 0.01C and the charging cut-off voltage was 4.0V; after charging was completed, the device was disassembled to remove the positive electrode material paste, and after cleaning with DMC, it was dried in an oven at 40°C for 5 hours.
[0052] (2) Weigh Cr8O according to the mass ratio of 87:5.5:0.5:7 21 , conductive carbon black, carbon nanotubes and polyvinylidene fluoride, add appropriate amount of NMP and transfer to the slurry barrel of the homogenizer, stir at low speed 45rpm and high speed 3000rpm for 4h, add NMP to adjust the slurry solid content to 50%, stir at low speed 45rpm and high speed 3000rpm for 2h, and keep the vacuum degree at -0.08MPa to -0.05MPa during the whole homogenization process. Finally, the first material layer slurry is obtained.
[0053] (3) The mixture obtained after precharging in step (1) and polyvinylidene fluoride were weighed at a mass ratio of 98:2, and an appropriate amount of NMP was added and transferred to the slurry barrel of the homogenizer. After mixing for 4 hours at a low speed of 45 rpm and a high speed of 3000 rpm, NMP was added to adjust the slurry solid content to 65%, and the mixture was dispersed for 2 hours at a low speed of 45 rpm and a high speed of 3000 rpm. The vacuum degree was maintained at -0.08 MPa to -0.05 MPa during the whole homogenization process. Finally, the second material layer slurry was obtained.
[0054] (4) Aluminum foil with a material of 1100 and a thickness of 0.012 mm was used as the current collector. The transfer coating method was used with a coating speed of 2000 mm / min and an oven temperature of 100-140°C. The first material layer slurry was coated on both sides of the current collector with a coating amount of 20 mg / cm 2 .
[0055] (5) The second material layer slurry is coated on the surface of the first material layer at a coating speed of 2000 mm / min, the oven temperature is set at 100-140°C, and the coating amount is 10 mg / cm 2 .
[0056] (6) The electrode obtained in step (5) is rolled to a compaction density of 3.0 g / cm 3 .
[0057] (7) Laser etching is performed on the outermost second material layer on both sides of the pole piece obtained in step (6) to form seepage guide grooves. The etching scheme is: a plurality of seepage guide grooves are formed throughout the width direction of the pole piece, the width of the seepage guide grooves is 1mm, the depth is 20um, and the total area of the plurality of seepage guide grooves accounts for 5% of the total area of the pole piece. The laser power is 30W, the wavelength is 1um, and the etching speed is 500mm / s. Finally, the attached Figure 2 The double-layer double-height electrode shown.
[0058] The double-layer double-high type electrode prepared in this embodiment is laminated with metal lithium and 16μm polyolefin diaphragm to form an 80Ah dry cell, which is then packaged in a square aluminum shell to form a reserve lithium battery. The battery is activated and discharged. The timing starts when the electrolyte is injected. After 10s of injection, the discharge starts at 1C. The battery discharge voltage exceeds 2.5V, and it has the ability to discharge externally. The final battery discharge specific energy reaches 380Wh / kg (excluding the activation system and electrolyte).
[0059] Example 2
[0060] Preparation of double-layer double-height electrode
[0061] (1) Weigh LiNi at a mass ratio of 95:1.5:0.5 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black and carbon nanotubes, after adding an appropriate amount of electrolyte, stir the above substances at a high speed of 3000rpm to obtain a paste positive electrode slurry; pour the paste positive electrode slurry into a charging device made of insulating material, insert a current collector made of aluminum metal, and cover the surface of the paste positive electrode slurry with a polyolefin material diaphragm with a thickness of 24μm. The size of the diaphragm should be larger than the inner cavity of the charging device so that the paste positive electrode slurry will not overflow from under the diaphragm; after adding an appropriate amount of electrolyte on the upper part of the diaphragm, place a metal lithium sheet containing a current collector as the negative electrode, cover the cover of the charging device to ensure internal sealing; use a charging and discharging device for pre-charging, the pre-charging current is 0.01C, and the charging cut-off voltage is 4.2V; after charging is completed, disassemble the device to take out the positive electrode material paste, clean it with DMC, and dry it in an oven at 40℃ for 5h.
[0062] (2) Cr2O5, conductive carbon black, carbon nanotubes and polyvinylidene fluoride were weighed in a mass ratio of 89:4:1:6, and an appropriate amount of NMP was added and transferred to the slurry barrel of a homogenizer. After mixing for 4 hours at a low speed of 45 rpm and a high speed of 3000 rpm, NMP was added to adjust the slurry solid content to 60%, and the slurry was dispersed for 2 hours at a low speed of 45 rpm and a high speed of 3000 rpm. The vacuum degree was maintained at -0.08 MPa to -0.05 MPa during the whole homogenization process. Finally, the first material layer slurry was obtained.
[0063] (3) The mixture obtained after precharging in step (1) and polyvinylidene fluoride were weighed at a mass ratio of 98:2, and an appropriate amount of NMP was added and transferred to the slurry barrel of the homogenizer. After mixing for 4 hours at a low speed of 45 rpm and a high speed of 3000 rpm, NMP was added to adjust the slurry solid content to 65%, and the mixture was dispersed for 2 hours at a low speed of 45 rpm and a high speed of 3000 rpm. The vacuum degree was maintained at -0.08 MPa to -0.05 MPa during the whole homogenization process. Finally, the second material layer slurry was obtained.
[0064] (4) Aluminum foil with a material of 1100 and a thickness of 0.012 mm was used as the current collector. The transfer coating method was used with a coating speed of 2000 mm / min and an oven temperature of 100-140°C. The first material layer slurry was coated on both sides of the current collector with a coating amount of 5 mg / cm 2 .
[0065] (5) The second material layer slurry is coated on the surface of the first material layer at a coating speed of 2000 mm / min, the oven temperature is set at 100-140°C, and the coating amount is 30 mg / cm 2 .
[0066] (6) The electrode obtained in step (5) was rolled to a compaction density of 3.15 g / cm 3 .
[0067] (7) Laser etching is performed on the outermost second material layer on both sides of the pole piece obtained in step (6) to form seepage guide grooves. The etching scheme is: a plurality of oblique seepage guide grooves are formed throughout the pole piece, the width of the seepage guide grooves is 1mm, the depth is 15um, and the total area of the plurality of seepage guide grooves accounts for 5% of the total area of the pole piece. The laser power is 30W, the wavelength is 1um, and the etching speed is 700mm / s. Finally, the attached Figure 3 The double-layer double-height electrode shown.
[0068] The double-layer double-high type electrode prepared in this embodiment is laminated with metal lithium and 14μm polyolefin diaphragm to form an 80Ah dry cell, which is then packaged in a square aluminum shell to form a reserve lithium battery. The battery is activated and discharged. The timing starts when the electrolyte is injected. The discharge starts at 5C 10s after the injection, and the discharge is carried out at 5C after 30s. During the entire discharge process, the battery discharge voltage exceeds 2.5V, and it has the ability to discharge externally. The 5C continuous discharge time can reach 600s, and the final battery discharge specific energy reaches 330Wh / kg (excluding the activation system and electrolyte).
[0069] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A double-layer double-height electrode, characterized in that: include: A current collector, a first active layer and a second active layer, wherein the first active layer is located between the current collector and the second active layer, the first active layer contains an energy-type active material, the second active layer contains a pre-charged power-type active material, and the open circuit voltage difference between the energy-type active material and the pre-charged power-type active material is ≤0.5V.
2. The double-layer double-height electrode according to claim 1, characterized in that: The energy-type active material includes Cr2O5, Cr3O8 and Cr8O 21 At least one of .
3. The double-layer double-height electrode according to claim 1 or 2, characterized in that: The pre-charged power type active material is obtained by pre-charging the power type active material with an initial state of charge = 0; the power type active material with an initial state of charge = 0 includes LiCrO2, LiCoO2, LiNiO2, LiNi a Co b Mn (1-a-b) O2 and LiNi a Co b Al (1-a-b) At least one of O2.
4. The double-layer double-height electrode according to claim 3, characterized in that: The first material layer contains a first conductive agent, and the second material layer contains a second conductive agent. The proportion of the first conductive agent in the first material layer is higher than the proportion of the second conductive agent in the second material layer.
5. The double-layer double-height electrode according to claim 4, characterized in that: The porosity of the first material layer is less than that of the second material layer; the porosity of the first material layer is 25% to 40%, and the porosity of the second material layer is 35% to 45%.
6. The double-layer double-height electrode according to claim 5, characterized in that: The first material layer contains a first binder, and the mass ratio of the energy-type active material, the first conductive agent and the first binder is (87-96): (2-6): (2-7).
7. The double-layer double-height electrode according to claim 5, characterized in that: The second material layer contains a second binder, and the mass ratio of the pre-charged power-type active material, the second conductive agent and the second binder is (92-98):(1-4):(1-4).
8. The double-layer double-height electrode according to any one of claims 1-2 and 4-7, characterized in that: The surface of the second material layer facing away from the first material layer is provided with a plurality of seepage diversion grooves, both ends of which extend to the side edges of the second material layer respectively, and the total area of the plurality of seepage diversion grooves accounts for 1% to 20% of the total area of the second material layer.
9. A method for preparing a double-layer double-height electrode, characterized in that: Includes steps: The power type active material with an initial state of charge = 0 is mixed with a second conductive agent and then pre-charged to obtain a pre-charged power type active material; Using an energy-type active material, a first conductive agent and a first binder to prepare a first material layer slurry with a solid content of 40 wt% to 60 wt%, coating the first material layer slurry on the surface of a current collector, and drying to obtain a first material layer; Using the pre-charged power-type active material, the second conductive agent and the second binder to prepare a second material layer slurry with a solid content of 50wt% to 70wt%, coating the second material layer slurry on the surface of the first material layer, drying and compacting to obtain the second material layer; On the surface of the second material layer, a plurality of liquid seepage guide grooves are constructed by laser etching to obtain a double-layer double-height electrode.
10. A reserve lithium battery, characterized in that: The positive electrode of the reserve lithium battery is a double-layer double-height electrode as described in any one of claims 1-8.
Citation Information
Patent Citations
Positive pole piece and electrochemical device
CN110943201A
Lithium ion secondary battery and method for producing the same
US20100075217A1
Pre-lithiated electrode plate and preparation method therefor, secondary battery, and electric device
WO2024016891A1
Cited By
Preparation method of composite current collector, battery monomer, battery device and power utilization device
CN120637500A
Preparation method of composite current collector, battery cell, battery device and power consumption device
CN120637500B